A Multimodal Approach to Restoring Motor Function After Spinal Cord Injury: Exploring the Use Of Plant-Based Biomaterials & Stimulating Propriospinal Interneurons - Couvrette, Lauren (Université d'Ottawa / University of Ottawa, 2025)
Spinal cord injury (SCI) presents a significant challenge in regenerative medicine due to its complex pathophysiology & extensive molecular barriers that hinder repair. Overcoming these challenges requires interdisciplinary strategies that combine molecular biology, bioengineering, neuroscience, and rehabilitative therapy. In particular, the neural tissue engineering approach aims to produce an implantable scaffold that can support regeneration of spinal cord tissue in the hopes of forming relay circuits or promoting the regrowth of native axons. These biomaterials can be engineered to create a favorable environment that facilitates axonal infiltration into the damaged regions of the central nervous system. This thesis explores the use of decellularized plant tissue as a biomaterial for 3D cell culture & neural tissue engineering. We first demonstrate the ability of plant-derived scaffolds to support proliferation of neural stem cells in vitro and guide their differentiation into the neuronal lineage. Subsequently, we assess the scaffold's potential to support motor recovery in a rat model of complete spinal cord injury. Our findings highlight a potential therapeutic application for plant-based biomaterials and show their ability to be functionalized with peptide coatings. Finally, we identify dI3 neurons as key contributors to the re-activation of spinal locomotor circuits in response to cutaneous sensory input below the injury. Together, these results highlight the promise of multimodal therapeutic strategies for motor recovery after spinal cord injury.